Contributing factors to motorcycle injury crashes in Victoria, Australia. (February 2017) - Allen, T.; Newstead, S.; Lenné, M.G.; McClure, R.; Hillard, P.; Symmons, M.; Day, L.
Highlights: We investigated the interaction between rider, other road user and environment factors in multi-vehicle crashes. Increasing rider age and lower traffic density were both associated with human error by the other road user (vs. rider). A secondary road design issue was associated with rider error (vs. other road user error) as the primary contributor. Inappropriate rider speed was associated with other forms of rider error (vs. other road user) in multi-vehicle crashes. For single-vehicle crashes, the road environment was judged as a secondary contributor in over three quarters of crashes. Abstract: Introduction: The increased popularity of powered two wheelers (PTWs) in Australia, combined with their vulnerability in the event of a crash, necessitates new strategies to prevent serious injury crashes. The purpose of this study was to use case-series data collected from a recent motorcycle case-control study to analyse contributing factors to crashes using a safe systems approach. Methods: A total of 235 injured riders were recruited and completed a questionnaire-based interview, each followed by a detailed inspection of the case motorcycle and crash site by a trained crash investigator. Primary and secondary contributors to the crash were judged based on all available information sources. Analysis of the most frequent contributing factors included separation of cases into single and multi-vehicle crashes. A stepwise logistic regression was used to test for factors associated with human error for multi-vehicle crashes. Results: Two thirds of crashes investigated involved another vehicle or road user(s). For multi-vehicle crashes the most common crash scenario involved another vehicle failing to give way to the rider, and the primary contributor was a perception failure or traffic scan error on the part of the other road user. A number of secondary factors were found to be significantly associated with human error type (other road user or rider error), including rider age, traffic density, inappropriate speed of the PTW, and a road design issue. For single vehicle crashes, the most common primary contributor was a misjudgement or control error on the part of the rider, with inappropriate speed as the most frequent secondary contributor. Conclusions: Despite the complexity of factors involved in PTW crashes resulting in injury, a number of significant associations exist between road users as the primary contributing factor (rider or other road user) and secondary factors, including rider age, traffic density, speed and road design issues.